Genetic background of melanoma – results of own studies and the literature data - Dębniak, Tadeusz; Maleszka, Romuald; Lubiński, Jan (Dermatology Review/Przegląd Dermatologiczny, 2011)
Malignant melanoma (MM) represents one of the most aggressive neoplasms and its frequency is rapidly increasing. Familial aggregations of this malignancy are present in around 3-15% of all cases. CDKN2A is the major “high-risk” MM susceptibility gene. Recently new selection criteria for CDKN2A genetic assessment of patients – the so-called mnemonic “guideline of three” – have been proposed: 1) individuals with three or more primary melanomas, 2) three or more melanomas among first or second degree relatives, 3) presence of three or more cases of melanoma and/or pancreatic cancer on the same side of the family. In the Polish population a common CDKN2A variant (A148T) significantly increases melanoma risk regardless of the cancer family history. A recent multi-centre genome-wide association study identified three loci strongly associated with melanoma risk: 16q24, 11q14-q21, 9p21. The list of mutations/polymorphisms which are believed to be associated with moderate MM risk includes: Lys751Gln_CC/Gly156Gly_CC of the XPD gene; R151C, V60L, R160C, R163Q of the MC1R gene; N991D of the BRCA2 gene and haplotype rs731236_A + rs1544410_T of the VDR gene. Appropriate management may reduce morbidity and mortality. Genetic testing and clinical evaluation should be performed, and family history should be obtained in all patients affected with MM, including those with apparently sporadic tumours.